Analysis of the Effectiveness of Local PMT Biscuits from Jewawut and Swallow's Nest in Improving the Nutritional Status of Toddlers: local food - Nur Husnul Khatimah; Alkhair Alkhair; Dea Zara Avila; Hairunnisah Hairunnisah; Muammar Iksan; Juraidin Juraidin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Malnutrition in children under five years of age remains a public health challenge in Indonesia, especially in rural areas. Efforts to improve nutritional status through the use of high-value local foods are one sustainable strategy. This study aims to analyze the effectiveness of providing biscuits made from millet and swallow nests in improving the nutritional status of children aged 1-5 years. This study used a pretest-posttest design without a control group with a sample size of 35 children selected purposively. The intervention was carried out for a certain period by providing millet and swallow nest biscuits every day. Nutritional status data were obtained through anthropometric measurements of weight and height, then analyzed using the Paired t-Test and McNemar's Test. The results showed a significant increase in the average nutritional status score of children from 13.45 ± 1.52 to 14.20 ± 1.47 (p = 0.000; p < 0.05). The McNemar test analysis also showed a significant change in the proportion of nutritional status (p = 0.042; p < 0.05), with a decrease in the proportion of malnourished children from 28.6% to 20.0%. These findings indicate that the consumption of millet biscuits and swallow nests has a positive effect on improving the nutritional status of children aged 1-5 years. Conclusion: The provision of jewawut biscuits and swallow nests is effective in improving the nutritional status of toddlers. The use of these local foods has the potential to become an alternative.